Multicultural-Based Public Policy: The Experience of Indonesia in Managing Diversity for National Resilience - Mashuri, Saepudin; Futaqi, Sauqi; Ruslin, Ruslin; Sugiyar, Sugiyar; Fakhrurrozi, Hatta; Rofiq, Ahmad Choirul (Technium Social Sciences Journal, 2024)
The management of societal diversity through multicultural-based public policies is an interesting issue that is developing in the democratic system of the Indonesian nation today. This research aims to analyze multicultural-based public policy in three elements such as managing diversity, democratic politics, and national identity in strengthening Indonesia's national resilience. Through a study of the intertextuality of documents on multicultural issues, this research analyzes library data related to the policy concepts, regulations, and responses of society to the practice of multicultural policies in the public sector. The findings of this research describe several multicultural policies that are difficult to implement in the democratic political system of Indonesia. It often deals with identity politics based on religion. To strengthen national identity, the Indonesian government applies two essential philosophies in all aspects of national life, namely Pancasila and Bhineka Tunggal Ika. Both contain strong multicultural values as the historical heritage of the Indonesian society which are continuously maintained through the policy of establishing the Pancasila Ideology Development Agency (BPIP). Multicultural-based public policies have strengthened national identity, nationalism attitude, social integration of society that supports the resilience of the Indonesian nation for unity in its diversity to date